Short- and Long-Term Outcomes in Patients With Right Ventricular Infarction According to Modalities of Reperfusion Strategies in China: Data From China Acute Myocardial Infarction Registry - Hu, Mengjin; Chen, Ge; Yang, Hongmei; Gao, Xiaojin; Yang, Jingang; Xu, Haiyan; Wu, Yuan; Song, Lei; Qiao, Shubin; Hu, Fenghuan; Wang, Yang; Li, Wei; et al. (Frontiers in Cardiovascular Medicine, 2022)
Purpose We sought to investigate the short- and long-term outcomes in patients with right ventricular infarction in China. Methods Data from China Acute Myocardial Infarction (CAMI) Registry for patients with right ventricular infarction between January 2013 and September 2014 were analyzed. Results Of the 1,988 patients with right ventricular infarction, 733 patients did not receive reperfusion therapy, 281 patients received thrombolysis therapy, and 974 patients underwent primary PCI. Primary PCI and thrombolysis were all associated with lower risks of in-hospital (3.1% vs 12.6%; adjusted OR: 0.48; 95% CI: 0.27–0.87; P=0.0151 and 5.7% vs 12.6%; adjusted OR: 0.43; 95% CI: 0.22–0.85; P=0.0155, respectively) and two-year all-cause mortality (6.3% vs 20.9%; adjusted HR: 0.50; 95% CI: 0.34–0.73; P=0.0003 and 11.0% vs 20.9%; adjusted HR: 0.59; 95% CI: 0.38–0.92; P=0.0189, respectively) compared with no reperfusion therapy. Meanwhile, primary PCI was superior to thrombolysis in reducing the risks of in-hospital atrial-ventricular block (4.2% vs 8.9%; adjusted OR: 0.46; 95% CI: 0.23–0.91; P=0.0257), cardiogenic shock (5.3% vs 13.9%; adjusted OR: 0.43; 95% CI: 0.23–0.83; P=0.0115), and heart failure (8.5% vs 23.5%; adjusted OR: 0.35; 95% CI: 0.22–0.56; P<0.0001). Primary PCI could reduce the risk of two-year major adverse cardiac and cerebrovascular event (19.1% vs 33.3%; adjusted HR: 0.72; 95% CI: 0.56–0.92; P=0.0092) relative to no reperfusion therapy, whereas thrombolysis may increase the risk of two-year revascularization (15.5% vs 8.7%; adjusted HR: 1.90; 95% CI: 1.15–3.16; P=0.0124) compared with no reperfusion therapy. Conclusions Timely reperfusion therapy is essential for patients with right ventricular infarction. Primary PCI should be considered as the default treatment strategy for patients with right ventricular infarction in the contemporary primary PCI era.